Probleme des Insolvenzplanverfahrens - Klaus Henselmann; Manuel Gutbier (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2010)
The paper analyses options in case of insolvency. Although insolvency plans empirically are very successful, they are not used very much. Reasons that prevent their application and possibilities for their promotion are discussed.
Keywords: G18; G33; G34; G38; K22; K35; M41; M42; 650; Insolvenz; Insolvenzplan; Insolvenzverwalter; Planinitiativrecht; Gläubigerversammlung; Entscheidungssituation; Pre-Packaged-Plan; Eigenverwaltung; insolvency; bankruptcy code; liquidation; liquidator; insolvency plan; chapter 11 plan; Pre-Packaged-Plan